Successful Strategies To Improve The Quality Of Graduates Through Quality Management - Mustajib; Darusalam (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The quality of education is determined by the application of the curriculum used and supported by qualified resources in all fields, therefore realizing the quality/quality of education requires mutually supportive cooperation between programs used together with resources that have integrity. This study aims to discuss more deeply how the implementation of quality management improves the quality of graduates, with details: 1) How does learning planning improve the quality of graduates? 2) How to implement learning quality management to improve the quality of graduates 3) How to evaluate and improve learning quality management. Type of qualitative research with a case study approach. Data sources in this study are primary data and secondary data. In their research, researchers used observation, interview, and documentation methods. Data analysis techniques that researchers use are data reduction, data presentation, conclusion, or verification. As for checking the validity using source triangulation and method triangulation. Research results: 1) Learning planning to improve the quality of graduates includes determining techniques, strategies, and learning media. 2) Implementation of learning quality management to improve the quality of graduates through internal programs including regular madrasah programs, skills madrasah programs, research madrasah programs, and extracurricular activities. Media used in delivering material using cellphones, whiteboards, and notebooks. 3) Evaluation and efforts to improve learning quality management with test instruments, including by providing daily, semester, and year-end test questions, and assessments every three months. And non-test evaluations are carried out Evaluation of which syllabus should be established and which is not appropriate